Improved properties of Pepper (Pepper nigrum L.) using Mutagen Ethyl Methane Sulphonate (EMS) - Iman Suswanto; Indri Hendarti; Tris Haris Ramadhan (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
The study aimed to determine the LC50 using EMS on pepper and obtain a better mutant than the parents. The material used was Indian variety pepper, and the chemical mutagen was Ethyl Methane Sulphonate (EMS). Two hundred Indian Cultivar pepper seeds obtained from community gardens were treated with EMS mutagen at a concentration of 0; 0.2; 0.4; 0.6; 0.8, and 1.0% with 3 hours of immersion. Observations consisted of germination, mutagen damage and agronomic characters. The LC50 calculation was obtained from the regression relationship of dead sprouts with several doses of EMS application which had the best fitting curve with the highest determination value (R2). The results showed that pepper germination was relatively low (62%). The impact of using EMS mutagens causes growth inhibition or even death of sprouts. The higher the concentration, the higher the mortality rate. The relationship between the concentration of mutagens and the mortality rate follows the polynomial equation y = 188.45x – 97.21x2 + 2.71 with a determination value of 99%. Based on the regression model, the LC50 value is 0.3%. In this study, the EMS concentration of 0.2% succeeded obtaining a better mutant pepper than the parental. indicated by increasing the length and width of the cotyledons, respectively, 20 and 24% greater than the control.